Perancangan Sistem Informasi Investasi Program Penanaman Jagung Hibrida PT. Tarum Sinergi Indonesia - Trianto, Topan (Jurnal Dimamu, 2025)
Hybrid corn planting is one of PT. Tarum Sinergi Indonesia's investment programs that aims to increase productivity and profits for the company. However, data and information management related to this investment program is still done manually. This study aims to design an investment information system that can facilitate data management, monitoring, and decision making in the hybrid corn planting program. The research method used is the waterfall method, which consists of needs analysis, system design, implementation, testing, and maintenance. The results of the investment information system design include planning, implementation, monitoring, and evaluation modules for the hybrid corn planting program. This system is expected to increase efficiency, effectivenes s, and more precise decision making in the hybrid corn planting investment program of PT. Tarum Sinergi Indonesia.